Antidiabetic medications and the risk of prostate cancer in patients with diabetes mellitus: A systematic review and meta-analysis - Haiying Cui; Yao Wang; Shuo Yang; Guangyu He; Zongmiao Jiang; Xiaokun Gang; Guixia Wang (Elsevier, 2022)
Background: Antidiabetic medications (ADMs) may modify prostate cancer (PCa) risk in patients with diabetes mellitus (DM). Accordingly, the current study assessed the possible associations between ADMs and the risk of PCa in diabetics. Methods: A systematic literature search (PubMed, Embase and Cochrane Library) identified studies evaluating the associations between ADMs and incidence of PCa. A meta-analysis followed PRISMA was performed using odds ratio (OR) with 95% confidence interval (CI) as effect measures. Results: In total of 47 studies involving 3094,152 patients with diabetes were included. Results of meta-analysis of the observational studies suggested no significant association between metformin, thiazolidinediones, sulfonylureas, insulin or dipeptidyl peptidase-4 inhibitors administration and the risk of PCa (All p-values > 0.05). Separate analysis of randomized controlled trials (RCTs) revealed a significant reduction in PCa risk with thiazolidinediones (OR = 0.55, p = 0.04) or glucagon-like peptide-1 receptor agonists (GLP-1RA) administration (OR = 0.53, p = 0.006), whereas no significant association was found in SGLT2 inhibitors (p = 0.3). Conclusion: Thiazolidinediones or GLP-1RA administration may have benefits in PCa based on RCTs, however, further research is needed to confirm these findings.